Navigating the politics of transformational adaptation in international climate negotiations - Biesbroek, Robbert; Broek, E.; Engbersen, D.; van Deursen, M.; Agarwal, R.; Thomas, Adelle; Mukherji, Aditi; Njuguna, Lucy (2025)
Transformational adaptation to climate risks is an emerging topic in international climate negotiations. However, political views diverge on the desirability and feasibility of introducing transformational adaptation as a new concept. While scientific efforts to clarify its meaning are necessary, only by critically reflecting on the political nature of the concept can the negotiations move forward.